Guided Endodontic Surgery: A Narrative Review - Azhar Iqbal; Thani Al Sharari; Osama Khattak; Farooq Ahmad Chaudhry; Alzarea K. Bader; Muhammad Mudassar Saleem; Rakhi Issrani; Ibrahem T. Almaktoom; Raghad Fayez H. Albalawi; Ebtehal Dhyab M. Alserhani (Medicina, 2023)
Background and objectives: Endodontic surgery has evolved over the last two decades. The use of state-of-the-art guided endodontic surgical procedures produces a predictable outcome in the healing of lesions of endodontic origin. The main objective of this review paper is to define and characterize guided surgical endodontics as well as its benefits and drawbacks by reviewing the most recent relevant scientific literature. Methods: A literature search was conducted using multiple databases comprising of MEDLINE (via PubMed), EMBASE, and Web of Science. The terms used for the search were ‘guided endodontics’, ‘surgical endodontics’, and ‘endodontic microsurgery’. Results: In total, 1152 articles were obtained from the analysis of the databases. Unrelated articles from the available full text of 388 articles were excluded. A total of 45 studies were finally included in the review. Conclusions: Surgical-guided endodontics is a relatively new area of study that is still maturing. It has many applications such as root canal access and localization, microsurgical endodontics, endodontic retreatment, and glass fiber post removal. Additionally, it does not matter how experienced the operator is; the procedure can be completed for the patient in less time and provides greater accuracy and safety than conventional endodontics.